2022
DOI: 10.1099/ijsem.0.005573
|View full text |Cite
|
Sign up to set email alerts
|

Arcanobacterium buesumense sp. nov., isolated from an anal swab of a male harbour seal (Phoca vitulina)

Abstract: A polyphasic taxonomic study was performed on an unidentified previously described Arcanobacterium -like Gram-positive strain 2701T isolated from an anal swab of a dead male harbour seal. Comparative 16S rRNA sequencing showed that the bacterium belonged to the genus Arcanobacterium in the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In harbor seals and other marine mammals, Arcanobacterium phocae is widespread and sometimes associated with wound infections ( 6 , 7 ). Routine microbial diagnostic investigations performed as part of a program monitoring harbor seals in the German North Sea revealed that harbor seals also appear to be a natural reservoir for other Arcanobacterium species, as three novel species were identified—namely, Arcanobacterium phocisimile ( 8 , 9 ), A. buesumense ( 10 , 11 ), and A. pinnipediorum ( 1 , 12 ).…”
Section: Announcementmentioning
confidence: 99%
“…In harbor seals and other marine mammals, Arcanobacterium phocae is widespread and sometimes associated with wound infections ( 6 , 7 ). Routine microbial diagnostic investigations performed as part of a program monitoring harbor seals in the German North Sea revealed that harbor seals also appear to be a natural reservoir for other Arcanobacterium species, as three novel species were identified—namely, Arcanobacterium phocisimile ( 8 , 9 ), A. buesumense ( 10 , 11 ), and A. pinnipediorum ( 1 , 12 ).…”
Section: Announcementmentioning
confidence: 99%